2021
DOI: 10.3390/polym13172926
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Interfacial Conductive Networks Formed in Carbon Black-Filled PA6/PBT Blends

Abstract: Interfacial localization of carbon fillers in cocontinuous-structured polymer blends is well-known as a high-efficiency strategy for conductive network formation. However, a comparison with interfacial localization of carbon fillers in sea-island-structured polymer blends is lacking. Here, three types of highly efficient conductive networks formed on the basis of interfacial localization of carbon black (CB) in polyamide 6 (PA6)/poly(butylene terephthalate) (PBT) blends with different blend compositions (80/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Only nanofillers well-dispersed in the polymer matrix result in the formation of a percolation network able to conduct electric current and shield electromagnetic waves. Due to the modification of the processing parameters, the state of nanofillers' dispersion can be controlled, and the final composite properties have a tunable morphology [17,18]. This, together with the chemical and corrosion resistance, low weight, flexibility, ease of processing into various shapes, and inexpensiveness, is why polymer composites have the potential to replace the metallic materials in EMI shielding applications [2,17,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Only nanofillers well-dispersed in the polymer matrix result in the formation of a percolation network able to conduct electric current and shield electromagnetic waves. Due to the modification of the processing parameters, the state of nanofillers' dispersion can be controlled, and the final composite properties have a tunable morphology [17,18]. This, together with the chemical and corrosion resistance, low weight, flexibility, ease of processing into various shapes, and inexpensiveness, is why polymer composites have the potential to replace the metallic materials in EMI shielding applications [2,17,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In our experience of other blends such as PP-PET, in compositions such as 60:40 and 50:50, a co-continuous morphology with sharper contrast is obtained even without selective etching, and the domain sizes are in the range of 5–10 μm instead of 500 nm. Li et al’s work [ 10 ] on carbon black in PA6/PBT blends showed a very good example of a co-continuous morphology with 50:50 PA6:PBT; contrast was improved by etching the PBT component with alcoholic KOH. However, the phase domains were tens of microns in width, rather than 500 nm or lower as in 60/40 PBT/PET ( Figure 14 b).…”
Section: Resultsmentioning
confidence: 99%
“…Mamunya et al [ 7 ] had shown that on compression moulding of poly(vinyl chloride) powder with metal particles, the condition for the formation of the ‘segregated network’ was that the conductive particle should be very much smaller in diameter than the polymer particle. Likewise, in cases where a segregated network was achieved with conductive particles in a polymer blend, such as the work of Li et al [ 10 ] using carbon black in a PA6/PBT blend, the conductive particles (carbon black) had dimensions of ~100 nm while the polymer domains in the blend (whether it was sea-island or co-continuous) were typically several microns in size. This allowed the conductive particles to nestle in the regions between domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that forming interfacial networks of conductive fillers in polymer blends is a high-efficiency approach to decrease conductive filler loadings. 14,[17][18][19][20][21][22][23][24][25][26][27][28][29][35][36][37][38][39][40][41] However, it is hard to construct interfacial networks of CB in PC-based binary blends because up to now it is impossible to find another polymer that has counterbalanced interaction with CB to PC. In our previous work, 39 we found that CB could form high-efficiency sea-island-type interfacial networks in poly(m-xylene adipamide) (MXD6)/poly(ethylene terephthalate) (PET) blends.…”
Section: Introductionmentioning
confidence: 99%